Mineralisation of atmospheric CO2 in hydromagnesite in ultramafic mine tailings – Insights from Mg isotopes. (15th September 2021) - Oskierski, Hans C.; Turvey, Connor C.; Wilson, Siobhan A.; Dlugogorski, Bogdan Z.; Altarawneh, Mohammednoor; Mavromatis, Vasileios
Abstract: In this study we present the first Mg isotope data that record the fate of Mg during mineralisation of atmospheric CO2 in ultramafic mine tailings. At the Woodsreef Asbestos Mine, New South Wales, Australia, weathering of ultramafic mine waste sequesters significant amounts of CO2 in hydromagnesite [Mg5 (CO3 )4 (OH)2 ·4H2 O]. Mineralisation of CO2 in above-ground, sub-aerially stored tailings is driven by the infiltration of rainwater dissolving Mg from bedrock minerals present in the tailings. Hydromagnesite, forming on the surface of the tailings, has lower δ 26 Mg ( δ 26 MgHmgs = −1.48 ± 0.02‰) than the serpentinised harzburgite bedrock ( δ 26 MgSerpentinite = −0.10 ± 0.06‰), the bulk tailings ( δ 26 MgBulk tailings = −0.29 ± 0.03‰) and weathered tailings containing authigenic clay minerals ( δ 26 MgWeathered tailings = +0.28 ± 0.06‰). Dripwater ( δ 26 MgDripwater = −1.79 ± 0.02‰) and co-existing hydromagnesite ( δ 26 MgHmgs = −2.01 ± 0.09‰), forming in a tunnel within the tailings, and nodular bedrock magnesite [MgCO3 ] ( δ 26 MgMgs = −3.26 ± 0.10‰) have lower δ 26 Mg than surficial fluid ( δ 26 Mg = −0.36‰) and hydromagnesite. Complete dissolution of source minerals, or formation of Mg-poor products during weathering, is expected to transfer Mg into solution without significant alteration of the Mg isotopic composition. Aqueous geochemical data and modelling of saturation indices, along with Rayleigh distillation and mixing calculations, indicate that the 26 Mg-depletion in the drip water, relative to surficial water, is the result of brucite dissolution and/or precipitation of secondary Mg-bearing silicates and cannot be assigned to bedrock magnesite dissolution. Our results show that the main mineral sources of Mg in the tailings (silicate, oxide/hydroxide and carbonate minerals) are isotopically distinct and that the Mg isotopic composition of fluids and thus of the precipitating hydromagnesite reflects both isotopic composition of source minerals and precipitation of Mg-rich secondary phases. The consistent enrichment and depletion of 26 Mg in secondary silicates and carbonates, respectively, underpins the use of the presented hydromagnesite and fluid Mg isotopic compositions as a tracer of Mg sources and pathways during CO2 mineralisation in ultramafic rocks.